Identification and Analysis of the Information and Computation Technologies' Dimensions in the Mathematics Classrooms in the Teachers Education Context Identificação e Análise das Dimensões que Permeiam a Utilização das Tecnologias de Informação e Comunicação nas Aulas de Matemática no Contexto da Formação de Professores - Rosana Miskulin; Geraldo Perez; Mariana da R. C. Silva; Camila Montrezor; Cristiane Santos; Eduard Toon; Paulo Liboni Filho; Pedro Henrique Santana (Universidade Estadual Paulista, 2008)
The development of Information and Computer Technologies (ICT) provides another dimension to the educational process, which transcends the inappropriate paradigms of traditional education characterized by programmed instruction, transmission of information, and "training" of mechanical reasoning. This other dimension gives priority to a new knowledge that considers creative thought as a basic aspect of human cognition. The mathematical educator assumes a fundamental role when seeking to make the methods of education and theories of work compatible with information technologies and communication, making them integral parts of the student's reality. The aim of this study, developed from the course "Philosophy of Education: Issues in Mathematical Education", was to investigate and establish relations between the diverse ways that the schools work with technology in Mathematical Education. Through description and analysis of data extracted from responses to a questionnaire, the main proposal of this work is to identify and analyze the limits and potential of the various dimensions implicit in the process of implantation of the use of computers in the Mathematics classroom to contribute to the process of teacher education. Key-words: Information and Computation Technologies (ICT). Mathematics. Computers in classroom. O desenvolvimento das Tecnologias da Informação e Comunicação (TIC) proporciona uma outra dimensão ao processo educacional, a qual transcende os paradigmas não apropriados do ensino tradicional, pontuado pela instrução programada, transmissão de informações e "treinamento" do pensamento mecânico. Essa outra dimensão prioriza um novo conhecimento que considera o pensamento criativo como aspecto fundamental da cognição humana. O educador matemático assume um papel fundamental, na medida em que compatibiliza os métodos de ensino e teorias de trabalho com as Tecnologias de Informação e Comunicação, tornando-as partes integrantes da realidade do aluno. Este trabalho, desenvolvido a partir da disciplina Filosofia da Educação: Questões da Educação Matemática, buscou investigar e estabelecer relações entre as diversas maneiras que as escolas trabalham com a tecnologia na Educação Matemática. Por meio da descrição e análise dos dados extraídos da aplicação de questionários, a proposta deste trabalho é identificar e analisar os limites e potencialidades das diversas dimensões implícitas no processo de implantação do uso dos computadores na sala de aula de Matemática, visando contribuir para o processo de formação de professores. Palavras-Chave: Tecnologias de Informação e Comunicação (TIC). Matemática. Computadores em sala de aula.